Digital banking: is it convenient for everyone? - Sahrim, Azila; Ali, Asiah; Idris, Asma’ Rashidah; Kamarulzaman, Masrul Hayati; Zainal Abidin, Nurain Farahana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Back in those days, we still remember accompanying our parents to the bank, getting a queue number and waiting for it to be called. It is time-consuming, but we can ask the bank officer directly if there are any problems or if we need more information regarding any services offered by the bank. Even though some of our parents are illiterate, they do not have any trouble doing money transactions or withdrawals, with the assistance of the teller. Today, the rise of digital technology has significantly transformed the norms of conservative banking into digital banking. Conservative banking is being replaced by digital platforms that offer faster and convenient access to financial services. It is undeniable that the digitalisation of banking services is very practical in today’s world. However, we cannot deny the fact that digital banking somehow complicates the accessibility of banking services to a certain group of people.